Analisis Yuridis Manajemen Kerahasiaan Visum Et Repertum Tindak Pidana Kesusilaan Di Rumah Sakit Bhayangkara Bondowoso - Achmad Jaelani Rusdi; Ancah Caesarina Novi M; Y. A. Triana Ohoiwutun (Pascasarjana Universitas Jember, 2019)
confidentiality management of Visum et Repertum (VeR) is compulsory for health service facility as the executor and guarantor for its patient medical confidentiality that, VeR is executed merely by the authorities. Bhayangkara Hospital in Bondowoso is an institution under State Police of The Republic of Indonesia that is responsible for police medical administration including VeR. With regard to this, it is crucial that VeR confidentiality management should meet the regulation concerning victim’s privacy rights as the patient in health facility. Qualitative method was employed with empirical juridical approach obtained from observation and in depth interview with 11 informants determined by purposive sampling. The research findings reveals that the urgent of VeR confidentiality of the victims of decency crime adheres the Law of Witness and Victim Protection, law of child protection and Law of domestic violence. The VeR of the victim of decency crime in Bhayangkara Hospital in Bondowoso has obeyed the law in terms of victim confidentiality, management of execution, report and VeR medical records of decency crime. However, based on Law on Hospital and Ministry of Health’s Regulation on Medical Records, it is mentioned that Medical Records Unit is also supposed to be responsible for the management, reports, and VeR recording in Bhayangkara Hospital Bondowoso.Keywords: Management, confidentiality, decency crime, hospital, VeR